Time and quality efficiency of Scotch single malt whisky production: An empirical two-model DEA approach - Magnus Richter (VERLAG proWiWi e.V., 2017)
Production of Scotch single malt whisky requires at least 3 years of storage time. The majority of whiskies are stored for about 10-18 years, several sorts are matured for even up to 70 years. This can be justified by the common opinion that older whisky is 'better'. This paper gives a technological basis for whisky production by deriving an aggregate transformation function, which contains the production stages distilling, storing and bottling. This function identifies key levers as being relevant for efficiency analysis. Based on empirical data, it is shown that storage time does not contribute to whisky quality. Subsequently, Data Envelopment Analysis is used to measure the quality efficiency of 82 whiskies originating from 22 distilleries. The results indicate that quality efficiency can be increased by rejuvenating mid-aged whiskies in particular. Rationality would thus suggest storage periods of only 3 years, which increases operational efficiency at the same time.
urn:nbn:de:gbv:ilm1-2017200495
Keywords: 650